Publication of Historical Sources – Assessment, Approach, Interpretation. Case Study: Antiochus Cantemir’s Passport - Lilia Zabolotnaia (Codrul Cosminului, 2023)
This research focuses on the release of a previously unexplored historical document, Antiochus Cantemir's diplomatic passport, recently discovered in the Russian State Archive of Ancient Acts in Moscow. The inclusion of this authentic document in scholarly discourse is an important addition to Cantemir's family research. The investigation attempted not only to highlight one of the pages of Antiochus Cantemir's diplomatic activities but also to exploit, to a certain extent, the relevance of a representative documentary source for this era.